Clinical Features of Affective Disorders in Patients with Dementia - Shadmanova L. Sh. (Scientific Trends, 2024)
The relevance of the problem is determined by the high prevalence of mental disorders in older age groups. According to the World Health Organization (WHO), about 15% of people aged 60 years and older suffer from mental disorders (WHO, Mental Health and Elderly, Information Bulletin, April 2016). Affective and organic mental disorders are most common in older age groups. According to WHO estimates, the prevalence of affective disorders among individuals over 60 years old is on average 10-30% [WHO, 2012]. Depression symptoms in people with organic brain diseases (dementia) reach 30-50% prevalence [1,2,5], compared to 13.2% of elderly people without cognitive impairments [7].
Keywords: Psychoorganic disorders of depression in elderly patients with vascular diseases of the brain.